Social Safety Nets for Elderly Tea Garden Workers in Bangladesh - Shahjahan, Mohammad; Himel, Shahan Shahoriar; Maruf, Jubaer Ahmed; Islam, Mst. Sadia (Advances in Social Sciences Research Journal, 2025)
This study examines the living conditions and welfare challenges of elderly tea garden workers in Bangladesh, with a focus on the Malnichhara Tea Estate in Sylhet. Despite dedicating their lives to the tea industry, many remain excluded from state-led social protection programs. Using a qualitative case study approach, data were collected from 15 elderly workers through in-depth interviews, key informant interviews, observations, and documents review. Findings reveal that most of the workers live in persistent poverty, relying on minimal wages or small retirement rations. None had access to bank accounts, leaving them financially insecure and outside formal financial systems. Long years of strenuous labor and economic hardship have contributed to poor physical health and psychological stress. Although respected within their own community, they remain marginalized from broader society and government welfare schemes. The study highlights the need for targeted policy measures, including special allowances, healthcare support, financial inclusion, and integration into the National Social Security Strategy (NSSS).